Pengaruh Kompetensi Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Barang Milik Daerah (Studi Kasus Pada Dinas Komunikasi, Informatika Dan Statistik Provinsi Sumatera Barat) - Joni Zulfiandi; Febryandhie Ananda (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to determine the effect of human resource competency and information technology utilization on the quality of regional property reports (a case study at the Office of Communication, Informatics, and Statistics of West Sumatra Province). The method used in this study is quantitative, using primary data in the form of a questionnaire. In analyzing the data using SPSS 25 software, the sampling method used was purposive sampling of 52 ASN respondents from the Office of Communication, Informatics, and Statistics of West Sumatra Province. The analysis technique used is multiple linear regression. Based on the research results obtained, it shows that the competence of human resources and the use of information technology affect the quality of regional property reports at the Office of Communication, Informatics, and Statistics of West Sumatra Province..